THE IMPACT OF GREEN INTELLECTUAL CAPITAL ON SUSTAINED COMPETITIVE ADVANTAGE AND BUSINESS PERFORMANCE OF MSMES IN SOUTH KALIMANTAN - Novianty, Nadya; Yusri (Universitas Tulungagung, 2026)
This study aims to analyze the influence of green human capital, green structural capital, and green relational capital on MSME business performance, both directly and indirectly through sustained competitive advantage as a mediating variable. The study employs a quantitative approach using a survey method involving 400 MSME actors in South Kalimantan Province, selected through simple random sampling. Data were collected through questionnaires and analysed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results show that green human capital, green structural capital, and green relational capital have a positive and significant effect on sustained competitive advantage and MSME business performance. Furthermore, sustained competitive advantage has a strong effect on business performance and serves as a mediating variable in the relationship between the three dimensions of green intellectual capital and business performance. These findings indicate that the effective management of environmentally oriented resources, particularly human capital, plays a crucial role in enhancing competitiveness and improving MSME performance. This study suggests that sustainability-based strategies can be an effective approach for MSMEs to remain competitive in increasingly dynamic and environmentally demanding business environments.